Modeling composite effects of marine and freshwater processes on migratory species. Issue 7 (1st July 2019) - Friedman, Whitney R.; Martin, Benjamin T.; Wells, Brian K.; Warzybok, Pete; Michel, Cyril J.; Danner, Eric M.; Lindley, Steven T.
Abstract: Life histories of migratory species such as anadromous fishes make them particularly susceptible to composite effects of processes experienced across distinct habitats and life stages. Therefore, their population dynamics are difficult to quantify and manage without tools such as life‐cycle models. As a model species for which life‐cycle modeling is particularly useful, we provide an analysis of influential processes affecting dynamics of the Central Valley fall‐run Chinook salmon (CVFC) population ( Oncorhynchus tshawytscha ). This analysis demonstrates how, through identification of covariates that affect this population at each life stage and their relationship to one another, it is possible to identify actions that best promote sustainability for this anadromous species. We developed a life‐cycle model for CVFC examining primary processes influencing variability in observed patterns of escapement from 1988 to 2016. CVFC are a valuable fishery along the US West Coast; however, their natural population is a fraction of its historic size, and recent low escapements have resulted in substantial restrictions on the fishery. Our model explains 68.3% of variability in historic escapement values. The most influential processes include temperatures experienced during egg incubation, freshwater flow during juvenile outmigration, and environmentally mediated predation during early marine residence. This work demonstrates the need, and methodology, for considering the interactions between freshwater and marine dynamics when evaluating the efficacy of managerial practices in freshwater and the ocean, especially in the context of increased environmental variability, climate change, and dynamic predator populations. The methodology developed in this study can be used toward improved conservation and management of other anadromous fishes and migratory species.